2015
DOI: 10.1080/02699931.2015.1035229
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of facial expressions and body language to the rapid perception of dynamic emotions

Abstract: Correctly perceiving emotions in others is a crucial part of social interactions. We constructed a set of dynamic stimuli to determine the relative contributions of the face and body to the accurate perception of basic emotions. We also manipulated the length of these dynamic stimuli in order to explore how much information is needed to identify emotions. The findings suggest that even a short exposure time of 250 milliseconds provided enough information to correctly identify an emotion above the chance level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 32 publications
1
64
0
2
Order By: Relevance
“…Even the valence of the event (goal-congruent or not) is not reliably perceived in high-intensity faces: the exact same facial configuration can be attributed to extreme joy (the unexpected return of a child from military service), extreme distress (witnessing a terrorist attack), extreme pleasure (orgasm), or extreme pain (unanesthetized nipple piercing) with equal plausibility [33]. To disambiguate these emotions, observers rely on body posture (open arms, lifted chest [44]) or inferred appraisals of the event (“he won the race” [45]).…”
Section: Ambiguous Perception and Precise Predictionsmentioning
confidence: 99%
“…Even the valence of the event (goal-congruent or not) is not reliably perceived in high-intensity faces: the exact same facial configuration can be attributed to extreme joy (the unexpected return of a child from military service), extreme distress (witnessing a terrorist attack), extreme pleasure (orgasm), or extreme pain (unanesthetized nipple piercing) with equal plausibility [33]. To disambiguate these emotions, observers rely on body posture (open arms, lifted chest [44]) or inferred appraisals of the event (“he won the race” [45]).…”
Section: Ambiguous Perception and Precise Predictionsmentioning
confidence: 99%
“…Researchers have used different approaches to investigate this issue, by focusing, for example, on how the synchronization between multiple signals has a facilitation effect in the interaction between mothers and children (Gogate, Bahrick, & Watson, 2000) and on the relative contribution of each modality when they provide conflicting (Massaro & Egan, 1996) or congruent emotional information (Bänziger, Grandjean, & Scherer, 2009;Martinez, Falvello, Aviezer, & Todorov, 2015;Wallbott & Scherer, 1986). While it seems clear and reasonable that multimodal expressions would be better recognized than unimodal expressions, the specific role of each modality remains to be determined (Martinez et al, 2015;Paulmann & Pell, 2011). …”
mentioning
confidence: 99%
“…Additionally, the basic emotions cannot be fully perceived using only facial information; body cues add information, which disambiguates facial displays (Martinez, Falvello, Aviezer, & Todorov, 2016). Interestingly, Martinez and collaborators (2016) showed that anger, contrary to other basic emotions, might be perceived slightly better from the body alone than 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 from the face.…”
mentioning
confidence: 99%